Strengthening village forest management strategies in East Kolaka, Southeast Sulawesi, Indonesia - MUHAMMAD REZA SETIAWAN; DODIK RIDHO NURROCHMAT; HANDIAN PURWAWANGSA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Setiawan MR, Nurrochmat DR, Purwawangsa H. 2024. Strengthening village forest management strategies in East Kolaka, Southeast Sulawesi, Indonesia. Biodiversitas 25: 2945-2959. The livelihoods of village communities in East Kolaka, Southeast Sulawesi, Indonesia, are intricately linked to managing forest resources for production, protection, and conservation. A key form of this community-based forest management is the Village Forest, a unique concept that encircles the forest. This study is particularly important as it evaluates the institutional conditions of Ueesi Village Forest management, Ueesi Sub-district, East Kolaka District, Southeast Sulawesi Province. It also proposes alternative strategies and strategic priorities for strengthening village forest institutions, strategies that are not just beneficial but also urgently needed for the sustainability of the communities. The study's findings underscore the need for the active participation of all stakeholders in this process. The study employed a qualitative approach and structured interviews with stakeholders or critical informants involved in the Ueesi Village Forest management. Technical analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) and Quantitative Strategic Planning Matrix (QSPM) were used to identify the necessary management strategies. The study reveals that the most suitable strategy for strengthening village forest management institutions for Ueesi Village is a turn-around (WO) strategy, which leverages all external opportunities to address internal weaknesses. The main strategic priority is to create role models who can mobilize and encourage administrators of village forest management institutions and community members to actively participate in the Ueesi Village Forest's management actively, fostering a sense of shared responsibility. The low knowledge and capacity of village forest Management Institutions (LPHD) administrators and members and the lack of systematic government support are the reasons why LPHD Ueesi is not yet optimal. In addition to government support, support is also needed from NGOs, universities, and the business sector (BUMD and private). Therefore, it is crucial to design a strategy to strengthen appropriate management institutions to support the management of the Ueesi Village Forest, with the active involvement of all stakeholders.